A review of electrohydraulic independent metering technology. (March 2020) - Abuowda, Karem; Okhotnikov, Ivan; Noroozi, Siamak; Godfrey, Phil; Dupac, Mihai
Abstract: The subject of this paper is the review of advanced technology used in hydraulic systems. The technology in question is termed Independent Metering (IM); this is used in hydraulically driven mobile machinery, such as agricultural, construction, municipal, and forestry vehicles. The idea behind the concept is to modify the connection between the actuator, which could be a cylinder or a motor, and a flow control valve. Traditionally, spool hydraulic valves were used to control the fluid flow into and out of hydraulic actuators. This keeps the meter-in and the meter-out of the actuator mechanically connected due to the construction of these valves. This connection makes the control system blind to pressure changes in one of the hydraulic chambers in the actuator. This, in turn, reduces the overall system controllability. It also increases energy losses, especially under an overrunning load. These two main weaknesses led researchers to break this mechanical connection and get into a new technology with different characteristics. The proposed technology was called Independent Metering. New and more complex control techniques can now be applied to the hydraulic systems using this technology that were not possible before or could be applied to more conventional servo design. This paper reviews Independent Metering (IM) and the technologies used or developed in this field to date. The paper reviews the state of art hydraulic technologies and indicates the links between them and IM. It also reviews the different types of hydraulic valves used when implementing IM. This review also discusses some control algorithms, IM layouts, IM challenges, and identifies where further improvements may be achieved. Highlights: Review the hydraulic Independent metering configurations. Investigate different technologies related to the IM. Show the main valves embedded into IM and their effects on the performance. Review the main IM control techniques and Layouts. Summarize the IM challenges and research trends.